PENGARUH STRUKTUR KEPEMILIKAN DAN TATA KELOLA PERUSAHAAN TERHADAP MANAJEMEN LABA - Febrianti, Seni (COMPETITIVE, 2023)
Earnings management is an act of engineering financial statements carried out by management with the aim of benefiting themselves. Earnings management occurs because managers prioritize personal interests even though they have to harm others. The use of effective corporate governance rules can help to reduce earnings management. The corporation requires an independent audit committee and a board of commissioners to develop an effective supervisory and control structure. In addition, earnings management behavior can be minimized by the existence of managerial and institutional ownership. The goal of this study is to see how managerial ownership, institutional ownership, the percentage of independent commissioners, and audit committees affect earnings management. The study method employed is a quantitative method with an associative approach that relies on secondary data, namely financial report data and annual reports of food and beverage manufacturing companies that are listed on the BEI. The findings show that managerial ownership (X1) and institutional ownership (X2) have a limited impact on earnings management (Y). Meanwhile, the proportion of independent commissioners (X3) and audit committees (X4) partially does not affect earnings management (Y). Simultaneously X1, X2, X3, and X3 have a significant effect on Y.